Psychological Tendencies of Students’ Personal Maturity Manifestations in the Process of Professional Training - Kordunova, Natalia; Potapchuk, Liudmyla (Psychological Prospects Journal, 2015)
The article presents theoretical and empirical analysis of personal maturity of students during their professional training. The article analyzes scientific approaches to understanding the concept of «personal maturity». The connection of such concepts as «maturity», «personality» is determined. It is indicated, that maturity is the longest period of personal development, which is characterized by tendency to achieve the highest mental, intellectual and physical abilities development. It is highlighted that personal maturity is psychological new formation of mature period of human life in the form of ontological core of personality, significant for ego-identity. It serves as simultaneously the criterion of personal growth and expression of personal human potential, its life stability in implementing its life strategy. The basic personality traits, that serve as indicators of personal maturity are singled out. The program of empirical research is developed and personal maturity components are studied, to promote the development of future specialists. Group of personal maturity components with high level of personal significance for gaining future profession is defined. Empirically determined, that in this age period, the formation of professionally significant characteristics of personal maturity is stillin progress and require correction during subsequent changes. The necessity of further studies of the obtained results is emphasized, to create programs of training sessions for student’s personal maturity components formation, according to their individual characteristics.